2011
DOI: 10.1002/adfm.201001613
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of the Sign of the Pyroelectric Effect in Quasi‐Amorphous SrTiO3 Films

Abstract: The magnitude and direction of the permanent electric polarization in the non‐crystalline, polar phase (termed quasi‐amorphous) of SrTiO3 in Si\SiO2\Me\SrTiO3\Me, (Me = Cr or W), Si\SrRuO3\SrTiO3, and Si\SrTiO3 layered structures were investigated. Three potential sources of the polarization which appears after the material is pulled through a temperature gradient were considered: a) contact potential difference; b) a flexoelectric effect due to a strain gradient caused by substrate curvature; and c) a flexoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Meanwhile, one might conclude, based on equation (96), that the application of a voltage between the electrodes will not lead to any bending of the plate. Indeed, 'naturally' assuming that the voltage produces a homogeneous polarization, no mechanical yield is seen from equation (96). Using similar reasoning, it was argued that a flexoelectric-based mechanical sensor, in contrast to piezoelectric-based devices, will not behave as an actuator [7,56].…”
Section: Flexoelectric Bendingmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, one might conclude, based on equation (96), that the application of a voltage between the electrodes will not lead to any bending of the plate. Indeed, 'naturally' assuming that the voltage produces a homogeneous polarization, no mechanical yield is seen from equation (96). Using similar reasoning, it was argued that a flexoelectric-based mechanical sensor, in contrast to piezoelectric-based devices, will not behave as an actuator [7,56].…”
Section: Flexoelectric Bendingmentioning
confidence: 99%
“…Recently, Lubomirsky and coworkers [75,[94][95][96] presented experimental data on perovskite thin films, which strongly suggest that a strain gradient can pole an amorphous material when it is thermally treated in a special way. It was shown that during such treatment the material is passing between two different amorphous states.…”
Section: Plastic Flexoelectricitymentioning
confidence: 99%
See 2 more Smart Citations
“…This can lead to a different behaviour at these interfaces and induce strain gradients which are the main cause of flexoelectric effect. The flexoelectricity studies in SrTiO 3 single crystals [21] and artificially strained layered structures [22] have been investigated by various methods. It was found [21] that the induced polarization can be decomposed into components, directed along different crystallographic directions, and in the vicinity of defects can be comparable with the ferroelectric polarization.…”
Section: Introductionmentioning
confidence: 99%